-54r-27p+36=

Simple and best practice solution for -54r-27p+36= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -54r-27p+36= equation:


Simplifying
-54r + -27p + 36 = 0

Reorder the terms:
36 + -27p + -54r = 0

Solving
36 + -27p + -54r = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -27p + -36 + -54r = 0 + -36

Reorder the terms:
36 + -36 + -27p + -54r = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -27p + -54r = 0 + -36
-27p + -54r = 0 + -36

Combine like terms: 0 + -36 = -36
-27p + -54r = -36

Add '54r' to each side of the equation.
-27p + -54r + 54r = -36 + 54r

Combine like terms: -54r + 54r = 0
-27p + 0 = -36 + 54r
-27p = -36 + 54r

Divide each side by '-27'.
p = 1.333333333 + -2r

Simplifying
p = 1.333333333 + -2r

See similar equations:

| 4(x+1)=4[x-(2-x)] | | -9+2x=7x-5-7x | | -6x=10-x | | -7(a+2)+15=1-7a | | 2-y=x-6 | | 2-(15-7)*7= | | 3-3=0.03703703703 | | 8-5+2-4+7*6= | | 1-0.75x-0.3x^2=0 | | e=3(8)+3(8) | | 5(t-3)-2t=3t-8 | | 5y+29=5+25 | | -8+5r=5r-r | | 18=21x-6y | | 99+5x=2000+-5x+911 | | 75-50x+6x^2=0 | | 15f-8f+13=-14 | | -7-7n=-6n-2n | | -32f-12g=48 | | 2(9-7s)= | | -5*y=x^2 | | 2r-y-6=0 | | 4k(7k+5)= | | 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 | | 7n+20=6 | | 200-6x=500-6x | | 4n+3+20=6 |

Equations solver categories